The Role of Amplitude Integrated Electroencephalogram in Very Low-Birth-Weight Preterm Infants: A Literature Review - Magalhães, Luiza Vieira da Silva; Winckler, Maria Isabel Bragatti; Bragatti, José Augusto; Procianoy, Renato; Silveira, Rita de Cássia Santos (Neuropediatrics, 2017)
Neurological sequelae are common in very low-birth-weight preterm infants. The prevention of brain injury and development of neuroprotective strategies have been the main objectives of modern neonatal neurology. Amplitude integrated electroencephalogram (aEEG) is a continuous brain monitoring method that can aid in early diagnosis and detect patients who are at risk. While its role in the assessment of full-term newborn infants is already well established, there are still doubts about its use in preterm infants. The objective of this review was to describe the main recommendations for the use of aEEG in very low-birth-weight preterm infants and its accuracy in assessing the prognosis and detecting epileptic seizures in this population.
Keywords: preterm newborn; outcome; monitoring; periventricular hemorrhage; leukomalacia